Bioinspired gradient hydrogel actuators with rewritable patterns and programmable shape deformation. Issue 32 (2nd August 2021) - Mo, Kangwei; Lin, Jiehan; Wei, Peng; Mei, Jin; Chang, Chunyu
Abstract : Our work provides a facile yet efficient strategy to fabricate hydrogel actuators with rewritable patterns and programmable shape deformations. Abstract : The botanical world inspires scientists to develop various smart actuators with diverse mechanical motions in response to external stimuli. However, it is challenging to obtain programmable and reversible hydrogel actuators. Herein, we presented a bioinspired nanocomposite hydrogel composed of poly(NIPAM- co -AA) and tunicate cellulose nanocrystals (TCNCs). A direct current electric field (DC-EF) was applied to induce controllable distribution of the TCNCs via electrophoresis for the formation of a gradient structure. To mimic the leaflet structure of Mimosa pudica, the patterns written using a lye pen on the hydrogel acted as the "pinnae" of leaves, while the residual regions worked as the "rachis" parts. With the increase of temperature, the "rachis" area of the nanocomposite hydrogel exhibited a large bending deformation because the gradient distribution of TCNCs induced asymmetric shrinkage, whereas the "pinnae" changed slightly because –COO − /–COO − electrostatic repulsion maintained the swelling state of the hydrogel network, like the leaflet folding of Mimosa pudica . Furthermore, these bioinspired hydrogel actuators with erasable and rewritable patterns exhibited programmable deformation, good stability, and good cycling performance. This work provided a facile yet efficient strategy for the fabrication of hydrogel actuators with rewritable patterns and programmable shape deformations.